Evaluating the implementation of a paediatric allergy-training programme in urban primary care centres in Cape Town, South Africa - Ortel, Randall Shane (Department of Public Health and Family Medicine, 2023)
Background: Approximately a third of South Africans have suffered from some allergic disease during their life, with the highest burden of morbidity occurring in childhood. Despite the incidence and prevalence of allergic diseases steadily increasing worldwide in the past few years, it has not yet been met with an increased capacity to treat these conditions. Inappropriate management in primary care, for instance, impacts patient quality of life and leads to increased health care costs, compounded by limited relevant learning opportunities for primary care practitioners (PCP). Studies in a South African context have demonstrated that inadequate management of allergic disorders in children results in unscheduled hospital visits, preventable admissions and a heavy reliance on tertiary allergy services. To address this, the Allergy Foundation of South Africa (AFSA) and Red Cross Children's hospital Allergy unit designed a hybrid in-service training programme in paediatric allergies for PCP's. The training consists of online modules, face-to-face seminars, in reach and outreach support. The aim of this study was to evaluate the implementation of this paediatric allergy training programme. Methods: A cross-sectional observational descriptive design with an analytical component was used. The study population were all staff members who registered for the training programme, with voluntary recruitment into the survey arm of the study. As this is programme-level data, exclusion criteria were not applied. Descriptive data were collected from registration and attendance registers, and survey data in the form of an online self-administered questionnaire which explored three domains: accessibility; relevance to practice and acceptability. Results: Three hundred and forty staff members registered for the training programme, and 89 participated in the survey by completing the self-administered questionnaire. Of the staff enrolled in the training programme, 215 were doctors, 66 were nurses, 2 were facility managers, and 2 were pharmacists. Job categories of 55 staff who registered could not be determined. The throughput rate for the online component was 35.3% (120/340), and for the practical's, it was 49.2% (59/120), with an overall throughput rate of 17.4% (59/340). Medical officers were more likely to complete the training programme (online component: OR 5.4, (95% CI) 1.54 – 21.3, p = 0.011; practical component: OR 4.37, (95% CI) 1.33 – 15.5, p = 0.18) when compared to the nurses in this study. Having easy access to the training programme (OR 2.42; 95% CI 1.48 – 4.39; p= 0.001), senior or mentor support (OR 1.54; 95% CI 1.05 – 2.29, p= 0.035), having enough allocated time to complete the programme (OR 5.34; 95% CI 2.88 – 11.8, p 0.9) for the training of this nature requiring regular coursework was not associated with the completion of the training programme. The roll-out of the training programme was significantly impacted by the COVID-19 pandemic, which prevented any further training from March 2020. Conclusions: This study showed that significant contextually relevant factors impact the implementation of innovations aimed at improving clinical quality in primary care. Developing a deep understanding of these barriers is essential in implementing sustainable quality improvement projects. The study achieved its key outcomes of describing the implementation of the training programme, measuring the accessibility, relevance to practice, the overall acceptability domains of the programme and identifying factors that were enablers or barriers to its implementation.